Odpowiedzi

2010-03-22T18:56:10+01:00
A 5(x-1)+2x=2(x+2)+6
5x-5+2x=2x+4+6
7x-5=2x+10
5x=15 :5
x=3
b x+4-5(x-8)=x-6
x+4-5x+40=x-6
-5x=-50
x=10
c 6x-(x-1)=6
6x-x+1=6
5x=5
x=1

d 2(x-1)+3(x-2)=7
2x-2+3x-6=7
5x=15
x=3
e 3(x+2)+2(2x-3)=x-12
3x+6+4x-6=x-12
6x=-12
x=-2
f x(x-2)-(X2-2x-3)=2x+1
x²-2x-x²+2x+3=2x+1
-2x=-2
x=1
1 5 1
  • Użytkownik Zadane
2010-03-22T18:57:02+01:00
A) 5(x-1)+2x=2(x+2)+6
5x-5+2x=2x+4+6
5x+2x-2x=5+4+6
5x=15 /:5
x=3

b)x+4-5(x-8)=x-6
x+4-5x-40=x-6
x-5x-x=40-4-6
-5x=30 /:(-5)
x=-6

c) 6x-(x-1)=6
6x-x+1=6
6x-x=6-1
5x=5 /:5
x=1

d)2(x-1)+3(x-2)=7
2x-2+3x-6=7
2x+3x=7+6+2
5x=15 /:5
x=3

e)3(x+2)+2(2x-3)=x-12
3x+6+4x-6=x-12
3x+4x-x=6-6-12
6x=-12 /:6
x=-2

f)x(x-2)-(X2-2x-3)=2x+1
x2-2x-x2+2x+3=2x+1
x2-x2-2x+2x-2x=1-3
-2x=-2 /:(-2)
x=1

w przykładzie f) x2 to jest x kwadrat
2 5 2